Physical activity, eating behaviours and body satisfaction among private preschoolers in Putrajaya / Woh Poh Then - Woh , Poh Then (2020)
Numerous studies had focused on examining the physical activity level, eating behaviours and body satisfaction worldwide. Additionally, some researchers have explored the gender differences of primary school students and adolescents as well as the correlation between these three variables. However, there are fewer studies that involve preschoolers and young children. Hence, the purpose of this study is to seek better understanding of the physical activity level, eating behaviour and body satisfaction among pre-schoolers in Malaysia. The Federal Territory of Putrajaya was being selected as the study’s location as it marked the highest percentage of children; and highest overweight and obesity rate in Malaysia. The researcher applied simple random sampling to select participants from the location. 120 participants aged 6 years old from 5 different private preschools, together with the assistance of their parents participated in this study. The participants responded to ‘Reported Snack Food Intake’ (adapted version) and ‘Children Figure Drawing’; while parents contributed to ‘Children’s Physical Activity Questionnaire (CPAQ)’ and ‘Child Eating Behaviour Questionnaire (CEBQ)’. The results showed that there was a gender difference in total sports time (p=0.000) but not total leisure, activities at school and sedentary activities. There were significant gender differences in both the eating behaviours’ subscales which included Food Approach Behaviour (p=0.045) and Food Avoidant Behaviour (p=0.000) as well as body satisfaction (p=0.000). The body dissatisfaction negatively correlates with the engagement in sport activities (r=-0.197, p=0.031); but positively correlates with Food Avoidant Behaviour (r=0.244, p=0.007). Since childhood is a critical and crucial period in a person’s lifespan, it is important for educators, parents and related parties to pay more attention to how physical activities, eating behaviours and body satisfactions have an effect on both the physical and psychological development of children.